(untitled) - Murphy, R. Taggart (New York, 1996)
In eight years from 1980 to 1988, America fell from financial grace, becoming the world's largest debtor. This happened because the United States spent and Japan saved. In the early 1980s, Reagan's Washington discovered that Japan would cheerfully lend their vast savings to the United States by buying U.S. government bonds. How the Japanese money accumulated, the system that created it, and American fumbling that led to crippling debt service, a loss of much of our manufacturing base, and our economy's diminishing good jobs. The Weight of the Yen explains it all, in an intriguing, jargon-free analysis of the past fifteen years and the problems between America and Japan that are yet to come.
Keywords: Investments, Japanese,Budget deficits,Đầu tư, Nhật Bản,Thâm hụt ngân sách; United States,United States,Hoa Kỳ,Hoa Kỳ